2019
DOI: 10.1021/acsptsci.9b00039
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic and Inflammatory Benefits of Sympathetic Down-Regulation with Zamicastat in Aged Spontaneously Hypertensive Rats

Abstract: The hyperactivity of the sympathetic nervous system (SNS) plays a major role in the development and progression of several cardiovascular diseases. One strategy to mitigate the SNS overdrive is by restricting the biosynthesis of norepinephrine via the inhibition of dopamine β-hydroxylase (DBH). Zamicastat is a new DBH inhibitor that decreases norepinephrine and increases dopamine levels in peripherally sympatheticinnervated tissues. The cardiometabolic and inflammatory effects of sympathetic down-regulation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“… Background Zamicastat (1) is an inhibitor of dopamine‐β‐hydroxylase, enzyme that catalyzes the hydroxylation of dopamine to norepinephrine in sympathetic nerves and adrenal medulla, and it was shown to increase the survival rate in the monocrotaline rat model of pulmonary arterial hypertension. Objectives The purpose of this study was to evaluate zamicastat clearance and metabolic profile in hepatocytes from different species (human, rat, dog, mouse and monkey) and to identify the CYP450 enzymes isoforms that are involved in zamicastat metabolism. Methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… Background Zamicastat (1) is an inhibitor of dopamine‐β‐hydroxylase, enzyme that catalyzes the hydroxylation of dopamine to norepinephrine in sympathetic nerves and adrenal medulla, and it was shown to increase the survival rate in the monocrotaline rat model of pulmonary arterial hypertension. Objectives The purpose of this study was to evaluate zamicastat clearance and metabolic profile in hepatocytes from different species (human, rat, dog, mouse and monkey) and to identify the CYP450 enzymes isoforms that are involved in zamicastat metabolism. Methods.…”
mentioning
confidence: 99%
“…Zamicastat (1) is an inhibitor of dopamine‐β‐hydroxylase, enzyme that catalyzes the hydroxylation of dopamine to norepinephrine in sympathetic nerves and adrenal medulla, and it was shown to increase the survival rate in the monocrotaline rat model of pulmonary arterial hypertension.…”
mentioning
confidence: 99%
“… Background Zamicastat is a dopamine‐β‐hydroxylase inhibitor (1), previously showed to increase the survival rate in the monocrotaline rat model of pulmonary arterial hypertension. Objectives The purpose of this study was to characterize the absorption, distribution and elimination of 14 C‐zamicastat in rat and dog, after single oral (p.o.) or intravenous (i.v.)…”
mentioning
confidence: 99%
“…Zamicastat is a dopamine‐β‐hydroxylase inhibitor (1), previously showed to increase the survival rate in the monocrotaline rat model of pulmonary arterial hypertension.…”
mentioning
confidence: 99%
“…The study by Igreja and colleagues 5 uses the preclinical, aged spontaneously hypertensive rat (SHR) model to explore the therapeutic potential of a relatively new dopamine βhydroxylase inhibitor, zamicastat, as a possible therapeutic strategy to reduce overactivity of the sympathetic nervous systema clinical condition that is commonly associated with essential hypertension and congestive heart failure. Consistent with early stage clinical trials, the authors found that a daily dosage of zamicastat for 9 weeks significantly decreased norepinephrine levels and improved overall cardiometabolic health in the aged SHR rats compared to nonhypertensive controls.…”
mentioning
confidence: 99%